Control de inventarios para optimizar el flujo operacional en Grupo Tropi - Garcia Foronda, Juan Camilo (Corporación Universitario Minuto de Dios, 2025)
Tropicana S.A.S., a distributor of mass consumer products, faces challenges in inventory management due to high demand variability and an uncertain supply chain. Factors such as globalization, digitalization, and unforeseen events (pandemics, conflicts, and natural disasters) have made it difficult to maintain a stable inventory flow. Additionally, the company experiences constant administrative changes, high staff turnover, and a lack of strategy for integrating technology, leading to high operating costs, customer dissatisfaction, and loss of competitiveness. It also faces payment issues with suppliers, further affecting supply chain stability. To address these challenges, it is recommended to implement an integrated work model incorporating predictive analysis tools, demand planning, and strengthened supplier relationships. With these strategies, Tropicana S.A.S. can enhance its competitiveness and ensure sustainable growth in the market.

Tropicana S.A.S., a distributor of mass consumer products, faces challenges in inventory management due to high demand variability and an uncertain supply chain. Factors such as globalization, digitalization, and unforeseen events (pandemics, conflicts, and natural disasters) have made it difficult to maintain a stable inventory flow. Additionally, the company experiences constant administrative changes, high staff turnover, and a lack of strategy for integrating technology, leading to high operating costs, customer dissatisfaction, and loss of competitiveness. It also faces payment issues with suppliers, further affecting supply chain stability. To address these challenges, it is recommended to implement an integrated work model incorporating predictive analysis tools, demand planning, and strengthened supplier relationships. With these strategies, Tropicana S.A.S. can enhance its competitiveness and ensure sustainable growth in the market. Keywords: Inventory management, demand variability, commercial globalization, standard operating procedures, competitiveness.
Identificar cómo la variabilidad en la demanda afecta la gestión de inventarios, analizando los factores críticos para mejorar la eficacia operativa y estratégica en Tropicana
Keywords: Inventory management; Demand variability; Commercial globalization; Standard operating procedures; Competitiveness; Gestión de inventarios; Variabilidad de demanda; Globalización comercial; Procedimientos operativos estándar; Competitividad